Spontaneous and radical-induced plasma membrane lipid peroxidation in differently oxidant-sensitive yeast species and its suppression by antioxidants - Krasowska, A; Lukaszewicz, M; Oświecimska, M; Witek, S; Sigler, K (Folia microbiologica, 2000)
Formation of thiobarbituric acid-reactive substances (TBRS; nmol/mg lipids) indicative of lipid peroxidation was measured in whole cells and in isolated plasma membrane lipids from three yeast species differing in oxidant sensitivity (Schizosaccharomyces pombe, Saccharomyces cerevisiae and Rhodotorula glutinis) after exposure to the Fenton reagent, FeII, H2O2, tert-butyl hydroperoxide (TBHP) and azo compounds (AAPH, ACHN). In whole cells, spontaneous TBRS formation rose in the sequence S. pombe < S. cerevisiae < R. glutinis (1:approximately 5:approximately 7). Oxidants increased the TBRS production 13-18 fold in the sequence FeII approximately TBHP > AAPH approximately ACHN approximately Fe-Fenton > H2O2. This increase need not be solely due to increased lipid peroxidation. In isolated plasma membrane lipids from all three species, the spontaneous TBRS production referred to 1 mg lipids was 9-13-fold higher than in whole cells. In S. pombe lipids, only TBHP increased the TBRS production. In lipids from S. cerevisiae and R. glutinis, all added oxidants increased the spontaneous TBRS production 2-3 times in the sequence TBHP > ACHN > AAPH > FeII > Fe-Fenton > H2O2. Oxidant-induced TBRS production in both whole cells and isolated membrane lipids was partially suppressed by the lipid peroxidation inhibitors 2,6-di-tert-butyl-4-methylphenol ("butylated hydroxytoluene"; BHT) and the newly synthesized PYA12 compound. Both agents were more effective in isolated lipids than in whole cells and against OH.-producing than against ROO.- or RO.-producing oxidants. Yeast membrane lipids, which are generally poor in polyunsaturated fatty acids, are thus subject to perceptible lipid peroxidation.
Keywords: buněčná membrána; Yeasts; Thiobarbituric Acid Reactive Substances; volné radikály; peroxidace lipidů; butylhydroxytoluen; Schizosaccharomyces; oxidancia; Antioxidants; Free Radicals; kvasinky; antioxidancia; Butylated Hydroxytoluene; Saccharomyces cerevisiae; Oxidants; Cell Membrane; Rhodotorula; Lipid Peroxidation; látky reagující s kyselinou thiobarbiturovou